2020
DOI: 10.21037/apm-20-906
|View full text |Cite
|
Sign up to set email alerts
|

Chinese medicine Bazi Bushen capsule improves lipid metabolism in ovariectomized female ApoE−/− mice

Abstract: Background: Dyslipidemia is one of the mechanisms of atherosclerosis (AS). Depletion of estrogen plays a key role in the pathogenesis of postmenopausal AS in women, and the blood lipid levels of women are closely related to endogenous estrogen levels. Phytoestrogens (PEs) exert estrogenic effects, including protection against AS, without the adverse effects of estrogen administration. Bazi Bushen capsule (BZBS) is a traditional Chinese medicine herbal compound prescription that has been shown to contain 11 uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 44 publications
2
31
0
Order By: Relevance
“…23,24 Bazi Bushen has been demonstrated to improve lipid metabolism, atherogenesis, ageing-related hypogonadism and ageing-associated cognitive impairments. [22][23][24][25] At the same time, these studies have also proven that Bazi Bushen could prevent skin senescence such as hair loss, skin atrophy and loose skin. However, the mechanism of Bazi Bushen on skin senescence remains largely unclear.…”
mentioning
confidence: 85%
“…23,24 Bazi Bushen has been demonstrated to improve lipid metabolism, atherogenesis, ageing-related hypogonadism and ageing-associated cognitive impairments. [22][23][24][25] At the same time, these studies have also proven that Bazi Bushen could prevent skin senescence such as hair loss, skin atrophy and loose skin. However, the mechanism of Bazi Bushen on skin senescence remains largely unclear.…”
mentioning
confidence: 85%
“…Our previous study found that BZBS contains 11 PEs, namely isoquercitrin, hyperoside, verbascoside, epimedin A, icariin, baohuosideⅠ, imperatorin, osthole, catalpol, deoxyschizandrin, schisandrin B (36). BZBS lowed serum lipid levels, and improved fatty acid metabolism in highfat diet-fed, ovariectomized female ApoE −/− mice (36).…”
Section: Contains Pes and Protects Blood Vesselsmentioning
confidence: 98%
“…Our previous study found that BZBS contains 11 PEs, namely isoquercitrin, hyperoside, verbascoside, epimedin A, icariin, baohuosideⅠ, imperatorin, osthole, catalpol, deoxyschizandrin, schisandrin B (36). BZBS lowed serum lipid levels, and improved fatty acid metabolism in highfat diet-fed, ovariectomized female ApoE −/− mice (36). Disturbance of lipid metabolism is one of the mechanisms of occurrence and development of AS (37,38), and PEs inhibit the progression of AS by improving lipid metabolism (39).…”
Section: Contains Pes and Protects Blood Vesselsmentioning
confidence: 99%
“…First, to explore the relationship between PF4 and osteoporosis, a classic osteoporotic animal model was established via ligaturing bilateral ovariectomy (OVX). Generally, 60 mice were split into 10 groups of 6 mice, and the ligation of bilateral OVX was undertaken using standard methods [32]. After surgery, euthanasia was performed on each group every two weeks (at least) until week 12.…”
Section: 3mentioning
confidence: 99%